1997
DOI: 10.1021/jp971183n
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Triplet Mechanism Spin Polarization Induced by the Addition of Hydrochloric Acid in the Photochemical System of Xanthone in Alcohol

Abstract: The hydrochloric-acid-addition effect on the photochemical reaction of xanthone in alcohol is studied by a time-resolved ESR technique. The CIDEP spectra of the transient radicals peculiarly reveal an enhanced absorption by the addition of hydrochloric acid, while the ordinary triplet mechanism of xanthone is known to be emissive. The spin-polarization inversion phenomenon is explained by the triplet mechanism induced by the excitation of a ground-state weak charge-transfer complex of xanthone and HCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 39 publications
3
21
2
Order By: Relevance
“…Apparently, in these systems there is a CIDEP mechanism that makes a dominating net absorptive signal contribution and a small signal component stemming from the RPM. The results are in agreement with CW TREPR results reported previously …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Apparently, in these systems there is a CIDEP mechanism that makes a dominating net absorptive signal contribution and a small signal component stemming from the RPM. The results are in agreement with CW TREPR results reported previously …”
Section: Resultssupporting
confidence: 93%
“…The polarization pattern shown in Figure a differs from the E/A* pattern previously found in a CW TREPR study of free radicals formed by the photolysis with 337 nm laser excitation of Xn in alcohols . Moreover, as shown in Figure a, with 2-methyl-1-propanol as solvent, the FT-EPR spectrum shows an almost symmetrical E/A pattern, whereas in previous TREPR work an E/A* type spectrum was observed.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…It seems that the signals from (CH3)2C'OH and PA'H rise immediately after laser excitation. However, the signal of PA'H grows even after the signal of (CH3)2C'OH starts to decay, whilst the decay of the alcohol radical is much faster than that observed in the system of TCPA presented in this paper and in different system [18] where no PA is present. The time profile suggests that the initial reaction is the hydrogen abstraction reaction from 2-propanol.…”
Section: Phthalic Anhydride In 2-propanolcontrasting
confidence: 53%
“…It is relevant to note that recent time-resolved EPR studies of the reaction of triplet state xanthone with alcohols revealed a small dependence of spin polarization on excitation wavelength [25,26]. In this case, it is known that intersystem crossing from the excited singlet state to the triplet state of xanthone is fast and may compete with vibrational deactivation and/or internal conversion processes within the singlet excited state manifold.…”
Section: Spectroscopic Data and Theoretical Calculations Indicate Thamentioning
confidence: 99%